Drug wars and coffee houses: the political economy of the international drug trade - Mares, David R. 19XX- (CQ Press)
The drug trade as a global and national phenomenon -- Analytic perspectives for explaining the drug trade -- Conceptualizing consumption : drug use and drug users -- The production of psychoactive substances -- Distribution : linking producers and consumers -- Money laundering : money makes the world go round -- The political economy of international drug strategies : going it alone or working together -- The United States : from crime reduction to drug war, 1968-1982 -- The Netherlands : from drug war to dynamic harm reduction, 1960-2002 -- Sweden : from harm reduction to drug war, 1965-1993.